The Impact of Distribution Channel Towards Sales Volume at PT. Domas Intiglass Perdana Tanjung Morawa - Benny Lim; Ika Puspa Satrianny; Tina Linda (Universitas Muhammadiyah Palu, 2023)
Besides having a good quality of product, the company has to know how to bring the product to the customers. It is useless if the company offers a good product but the customers are not able to obtain it easily and conveniently. To overcome that kind of problem, the company has to pay attention to the distribution channel. PT. Domas Intiglass Perdana Tanjung Morawa has an intermediatery (wholesaler) which is its subsidiary company to distribute the products. They got many complaints from the customers (retailers) such as there is a minimum amount of purchases, make delays in delivery, have a few types of products and lack of supporting service. The objective of this research is to assess the impact of distribution channel towards sales volume in the company as well as to determine how strong the impact between both of them. In conducting the research, the writer has chosen the descriptive study. To gather the data needed, the writer distributes questionnaires which consist of 10 questions to 52 samples. In this research, the writer used two variables, which is Distribution Channel (Variable X) and Sales Volume (Variable Y). Then the data will be tested and the results of the data are valid and reliable. The result for this study shown that there is impact of distribution channel towards sales volume at PT. Domas Intiglass Perdana Tanjung Morawa. It can be seen from the result of the test of determination which is 52.5%. It means the impact of distribution channel toward sales volume is as large as 52.5%. We can also see from the result of z hypothesis where 5.18 (zcount) > 1.96 (ztable). This means the null hypothesis (Ho) is rejected. So the writer can conclude that the distribution channel has impact towards the sales volume at PT. Domas Intiglass Perdana Tanjung Morawa.